Find the best solutions to your questions at Westonci.ca, the premier Q&A platform with a community of knowledgeable experts. Discover solutions to your questions from experienced professionals across multiple fields on our comprehensive Q&A platform. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
x ³ = 1
x ³ - 1 = 0
x ³ - 1³ = 0
Factorize the right side as a difference of cubes:
(x - 1) (x ² + x + 1) = 0
Then
x - 1 = 0 or x ² + x + 1 = 0
The first equation yields x = 1 as a root.
For the other equation, rearrange and complete the square to get the other two roots,
x ² + x + 1/4 = -3/4
(x + 1/2)² = -3/4
x + 1/2 = ±√(-3/4) = ± i √3/2
x = -1/2 ± i √3/2
x = (-1 ± i √3)/2
Since complex roots occurs in conjugate pairs, taking the sum of these two roots eliminates the imaginary part:
(-1 + i √3)/2 + (-1 - i √3)/2 = (-1 - 1)/2 = -2/2 = -1
and adding to 1 indeed shows that the sum of roots is zero.
Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Find reliable answers at Westonci.ca. Visit us again for the latest updates and expert advice.